2014
DOI: 10.1175/jcli-d-13-00469.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Cloud Response to the Gulf Stream Front in Winter Using CALIPSO*

Abstract: A sharp sea surface temperature front develops between the warm water of the Gulf Stream and cold continental shelf water in boreal winter. This front has a substantial impact on the marine boundary layer. The present study analyzes and synthesizes satellite observations and reanalysis data to examine how the sea surface temperature front influences the three-dimensional structure of low-level clouds. The CloudAerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) satellite captures a sharp low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
1
26
1
Order By: Relevance
“…This feature can alter the cloud field through other processes in addition to CAOs. The SST gradients near the Gulf Stream, resulting in strong heat flux gradients, can give rise to circulations resembling sea‐breeze fronts (Sublette & Young, ), with higher cloud tops toward the warm side of the front (Liu et al, ). The warmer SSTs can reduce the local atmospheric stability, affecting the low cloud field and modulating the surface winds through the vertical momentum flux (Chelton et al, ).…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…This feature can alter the cloud field through other processes in addition to CAOs. The SST gradients near the Gulf Stream, resulting in strong heat flux gradients, can give rise to circulations resembling sea‐breeze fronts (Sublette & Young, ), with higher cloud tops toward the warm side of the front (Liu et al, ). The warmer SSTs can reduce the local atmospheric stability, affecting the low cloud field and modulating the surface winds through the vertical momentum flux (Chelton et al, ).…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…This rectifying effect of storm-track activity on climatological SHF seems prominent around the Agulhas SST front. Note that submonthly atmospheric eddies may also be important for climatological-mean lowcloud top, since climatological cross-frontal contrast of low-cloud top around the SST front along the Gulf Stream resembles the corresponding contrast under cold advection events (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al . (), in an attempt to explain the enhancement of cloud cover and the increase of cloud‐top level over the Gulf Stream front, compared southerly and northerly regimes: under cold northerly advection, strong near‐surface instability led to a well‐mixed boundary layer over the Gulf Stream, causing a southward deepening of low‐level clouds across the SST front.…”
Section: Introductionmentioning
confidence: 99%
“…On the oceanic side, the Gulf Stream current, which flows along the North American continental margin, carries warmer waters northward, leading to strong sea-surface temperature (SST) gradients off the coast and further east. The SST front has a substantial impact on the marine atmospheric boundary layer above: QuikSCAT satellite data revealed increased wind speed over warmer waters and coherent structures of surface wind convergence along the SST gradient (Chelton et al, 2004), while CALIPSO satellite data captured a sharp low-level cloud transition across the front Liu et al, 2014). Minobe et al (2008) showed that the wind convergence in the boundary layer anchored a band of precipitation and was accompanied by vertical wind reaching the tropopause.…”
Section: Introductionmentioning
confidence: 99%